Effect of Time Dependent Stenosis on Blood Flow through an Arterial Segment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study deals with the influence of time dependent stenosis and slip velocityon blood flow through an arterial segment. The problem is investigated by a joint effort ofanalytical and numerical techniques. The expressions of wall shear stress, resistance to flow,axial velocity and volumetric flow rate are obtained. The graphical representations have beenmade to validate the analytical findings with a view of its applicability to stenotic diseases. It isnoticed that the resistance to flow and wall shear stress increases with the stenosis height.